Personalism in the Historiosophy of Feliks Koneczny - Sołga, Przemysław (Sensus Historiae, 2020)
The philosophy of history presented by Feliks Konieczny, one of the most famous Polish historians and philosophers of all times, was characterised by a strong focus on personalism, which was a key element of his grand historical narrative. This was a direct result of his attachment to Christian values and Christian theological views on the philosophy of history - which was directly linked with wider anthropocentric views and Catholic social teachings. Hence in his works, he highlighted the importance of values such as good, ethics, freedom, elitism and properly understood individualism, but also an showed inclination towards recognising capitalism and elitism. Spiritualism and a belief in a higher power were true sources of the virtues which defined this scholar from Vilnius, but also became a basis of his personalism.